2007
DOI: 10.4141/p05-223
|View full text |Cite
|
Sign up to set email alerts
|

Seeding rate, fertilizer level and disease management effects on hybrid versus open pollinated canola (Brassica napus L.)

Abstract: [255][256][257][258][259][260][261][262][263][264][265][266]. New canola cultivars have much higher yield potential than conventional canola cultivars and changes in production practices may be needed to achieve optimum yield from these cultivars. Studies were conducted to investigate the influence of seeding rates (2.8, 5.6 and 8.4 kg ha -1 ), fertilizer level (67% -low, 100% -medium, 133% -high of the commercial recommendation) and fungicide application on growth, dry matter accumulation, seed yield and seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
55
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 16 publications
10
55
2
Order By: Relevance
“…The effect of seed rate on the emergence m -2 of canola might be due to more seedlings emerged due to higher number of seeds sown. These results are in line with those of [17] who concluded that increasing seeding rate increased emergence in canola. In case of varieties, maximum emergence -2 was observed in Zahoor Swati as compared to Durr-e-NIFA.…”
Section: Figure 1 Biological Yield (Kg Ha -1 ) Of Canola As Affectedsupporting
confidence: 83%
“…The effect of seed rate on the emergence m -2 of canola might be due to more seedlings emerged due to higher number of seeds sown. These results are in line with those of [17] who concluded that increasing seeding rate increased emergence in canola. In case of varieties, maximum emergence -2 was observed in Zahoor Swati as compared to Durr-e-NIFA.…”
Section: Figure 1 Biological Yield (Kg Ha -1 ) Of Canola As Affectedsupporting
confidence: 83%
“…This is consistent with other studies completed in western Canada (Karamanos et al 2005;Brandt et al 2007;Gan et al 2007;). …”
Section: Seed and Seed Nitrogen Yieldssupporting
confidence: 82%
“…The cited earlier studies of spring-planted canola tested open-pollinated varieties, which have been shown to have considerably lower yield potential and fertilizer requirements than currently grown hybrids (Karamanos et al, 2005;Brandt et al, 2007;Smith et al, 2010). The cited earlier studies of spring-planted canola tested open-pollinated varieties, which have been shown to have considerably lower yield potential and fertilizer requirements than currently grown hybrids (Karamanos et al, 2005;Brandt et al, 2007;Smith et al, 2010).…”
Section: Yield Response To Early Defoliation In Spring-planted Canolamentioning
confidence: 99%